Evaluasi Pelatihan Pembuatan Media Interaktif Berbasis Powtoon Bagi Guru SD Muhammadiyah Berok Menggunakan Model CIPP - Yulistina, Nova; Rahmi, Ulfia; Eldarni, Eldarni; Yusri, Meldi Ade Kurnia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The evaluation of this training is needed to ensure the achievement of the goals that have been set. The evaluative approach used is to use the CIPP model which consists of context, process, and product. The method used in this study is the mixed methods method, which combines quantitative and qualitative methods to be used together in a research activity, so that more comprehensive, valid, reliable, and objective data is obtained. In the implementation of the training, the percentage of students obtained stated